Do I Talk Too Much in Class? A Quantitative Analysis of ESL Classroom Interaction - Kaukab Abid Azhar; Nayab Iqbal; Mahvish Sohaib Khan (OKARA: Jurnal Bahasa dan Sastra, 2019)
Teacher-learner interaction in the classroom is dictated by how well the teacher manages classroom talk-time which has a direct influence on learner achievement in an ESL Classroom. Teachers often perceive that they allocate enough time for student talk time; however, the past literature suggests that teacher talk-time takes around 70-75% of overall time in the class. The purpose of this study is to analyze the TTT (Teacher Talk-Time) in the context of ESL classroom in Pakistan. Convenience based sampling was used to assess the Teacher Talk-Time through observational method. Findings of 12 sessions (30-hours) showed that average Teacher Talk-Time was 65% of the total classroom time. The study highlights that ESL teachers need to improve the Learner Talk-Time (LTT) as the analysis showed that on average each student only gets 22 seconds of talk-time in an ESL class. A blended learning model can help ESL teachers to eliminate some of the talk-time and engage learners with meaningful activities that encourage classroom interaction in the target language.